1995
DOI: 10.1111/j.1399-3054.1995.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chloroplastic and cytosolic glutamine synthetase in barley leaves after cold‐sensitive blocking of β‐carotene synthesis by amitrole or mutation

Abstract: 3‐Amino‐ 1,2,4‐triazole (amitrole) provided to germinating barley at 20°C in the light led to bleached seedling leaves and photodynamic destruction of chloroplast structure, whereas normal greening and chloroplast ultrastructure was obtained when the seedlings developed in the presence of amitrole in the light at 30°C. Mass spectrometric analysis of the extractable herbicide demonstrated the same content of amitrole in leaves developed at 20 and 30°C. A very similar temperature‐sensitive syndrome is characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Previous research on AM‐treated barley plants has shown a partial recovery of carotenoid biosynthesis with an increase in growth temperature (Zito et al 1995; Agnolucci et al 1996; Rascio et al 1996), and the same temperature effect has been found in the barley lycopenic mutant tigrina‐o 34 (Casadoro et al 1983). In contrast, the temperature change did not affect the inhibition of carotenogenesis due to NF (La Rocca et al 1998; Dalla Vecchia et al 2001).…”
Section: Resultssupporting
confidence: 52%
“…Previous research on AM‐treated barley plants has shown a partial recovery of carotenoid biosynthesis with an increase in growth temperature (Zito et al 1995; Agnolucci et al 1996; Rascio et al 1996), and the same temperature effect has been found in the barley lycopenic mutant tigrina‐o 34 (Casadoro et al 1983). In contrast, the temperature change did not affect the inhibition of carotenogenesis due to NF (La Rocca et al 1998; Dalla Vecchia et al 2001).…”
Section: Resultssupporting
confidence: 52%
“…The idea was supported by the fact that among the carotenoids, lycopene exhibits the highest physical quenching rate constant with singlet oxygen, and in humans the level is higher than that of β‐carotene 1, 2. The phenomena that elevated oxidative stress by amitrole treatment led to lycopene accumulation had been observed in maize 48, 49, and barley 50. Oxidative stress induced by cupric ions also activated lycopene biosynthesis in tomato fruits 51.…”
Section: Discussionmentioning
confidence: 99%